Effect of lower respiratory tract infections on peak expiratory flow rate in children admitted to Rajarajeshwari medical college hospital, Bangalore, Karnataka, India - Y., Sree Krishna; Banik, Aditi; Hassan, Muhammed (International Journal of Contemporary Pediatrics, 2018)
Background: Peak expiratory flow rate is the simplest , cost effective and easily available test to assess the respiratory function. PEFR is measured by a peak expiratory flow meter. Measurement of PEFR is most commonly used for asthmatic patients. To evaluate the effect of lower respiratory tract infection on peak expiratory flow rate in children. Methods: PEFR were measured in eighty children suffering from LRTI by peak flow meter . Height and weight were measured. PEFR was compared with the normal charts. mean PEFR was calculated and predicted percentage of PEFR was calculated. Results: Mean PEFR in pneumonia , para pneumonic effusion, bronchiectasis, and bronchitis was 187.2 , 187.6, 171.85 and 173.1 respectively. Mean PEFR was maximally reduced in bronchiectasis and bronchitis. Mean PEFR was reduced in female children in comparison to males with LRTI. PEFR was decreased more in children with severe clinical presentation and with malnutrition. Conclusions: In this study , most common LRTI was pneumonia followed by parapneumonic effusion. PEFR was maximally reduced in bronchiectasis and bronchitis. Undernourished children were more affected.